Estudio de mejora aplicada en el área de control de gestión en una empresa fabricante de colchones - Lescano Martinez, Pedro Gregorio (2020)
The high competitiveness that exists today in the business world and the number of variables that we must take into account to know the situation and evolution of all the resources of a company has led us to develop management systems that respond to the complexity of the organization. These systems imply a definition of the information, its interpretation and the implementation of preventive models that help us make decisions. It is for this reason that Dreamfort Peru achieves the successful implementation of the Management Control area in the Peruvian subsidiary, generating considerable savings for the organization during the development of the project and up to now. As mentioned, this work will develop the implementation of the Management Control area within a mattress manufacturer company, going through the different stages that the creation and development of this area mean in the Peruvian subsidiary. The development of the project to improve and implement the Management Control area began in October 2018 and continues to date with new objectives and new goals for the comprehensive improvement of the organization. During the development of the project, different problems were found in the management of the control of expenses in the company, the lack of reports that serve as control and monitoring of budgets and levels of obsolescence and overdue inventories. The focus of the work was centered on the improvement of these main problems, improving and optimizing the company's expenses, creating control and managerial reports for the parent company and finally the optimization of obsolescence and lag inventory control. At the end of 2019, a savings in expenses versus the budget of 2.5 million soles was observed, a growth in the fulfillment of all the Dreamfort Peru indicators and a better integration between the different heads and managements of the company. Keywords: Management Control, Budgets, Expenses, Savings, Inventories, Improvement.